Fit for Developing Software Framework for Integrated Tests - Cunningham, Ward; Mugridge, Rick (Addison-Wesley Professional, 2005)
"The unique thing about Fit for Developing Software is the way it addresses the interface between customers/testers/analysts and programmers. All will find something in the book about how others wish to be effectively communicated with. A Fit book for programmers wouldn't make sense because the goal is to create a language for business-oriented team members. A Fit book just for businesspeople wouldn't make sense because the programmers have to be involved in creating that language. The result is a book that should appeal to a wide range of people whose shared goal is improving team communications." --Kent Beck, Three Rivers Institute "Even with the best approaches, there always seemed to be a gap between the software that was written and the software the user wanted. With Fit we can finally close the loop. This is an important piece in the agile development puzzle." --Dave Thomas, coauthor of The Pragmatic Programmer "Ward and Rick do a great job in eschewing the typical, overly complicated technology trap by presenting a simple, user-oriented, and very usable technology that holds fast to the agile principles needed for success in this new millennium." --Andy Hunt, coauthor of The Pragmatic Programmer "Florida Tech requires software engineering students to take a course in programmer testing, which I teach. Mugridge and Cunningham have written a useful and instructive book, which will become one of our course texts." --Cem Kaner, Professor of Software Engineering, Florida Institute of Technology "Rick and Ward continue to amaze me. Testing business rules is a fundamentally hard thing that has confounded many, and yet these two have devised a mechanism that cuts to the essence of the problem. In this work they offer a simple, thorough, approachable, and automatable means of specifying and testing such rules." --Grady Booch, IBM Fellow "By providing a simple, effective method for creating and automating tabular examples of requirements, Fit has dramatically improved how domain experts, analysts, testers, and programmers collaborate to produce quality software." --Joshua Kerievsky, founder, Industrial Logic, Inc., and author of Refactoring to Patterns "Agile software development relies on collaborating teams, teams of customers, analysts, designers, developers, testers, and technical writers. But, how do they work together? Fit is one answer, an answer that has been thoroughly thought through, implemented, and tested in a number of situations. P...
Online resource; Title from title page (viewed June 29, 2005)
Keywords: Computer software -- Evaluation; Software engineering; Logiciels; Évaluation; Génie logiciel; Computer software; Evaluation